2015
DOI: 10.4103/0253-7613.150340
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anti-osteoarthritic activity of Vigna mungo in papain induced osteoarthritis model

Abstract: Aim:This study was carried out to evaluate the effect of Vigna mungo hydroalcoholic extract (VMHA) by papain induced osteoarthritis (OA) in the rat model.Materials and Methods:OA was induced by intra-articular injection of papain (4% w/v) along with cysteine (0.03 M) on day 1, 4 and 7 in rats and VMHA was administered orally in three doses (100, 200 and 400 mg/kg) after last papain injection. The anti-osteoarthritic activity was evaluated by measuring knee joint diameter, grip strength, locomotion activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 9 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Along with these inflammatory cytokines, MMP levels and free radical products increase [ 15 ]. All of these factors induced by intra-articular injection of papain lead to arthritis symptoms in rabbits, which mimic the conditions found in human OA [ 16 ]. In this study, an OA-OCD rabbit model was established by intra-articular injection of papain followed by the creation of a cylindrical osteochondral defect in the femoral patellar groove.…”
Section: Introductionmentioning
confidence: 99%
“…Along with these inflammatory cytokines, MMP levels and free radical products increase [ 15 ]. All of these factors induced by intra-articular injection of papain lead to arthritis symptoms in rabbits, which mimic the conditions found in human OA [ 16 ]. In this study, an OA-OCD rabbit model was established by intra-articular injection of papain followed by the creation of a cylindrical osteochondral defect in the femoral patellar groove.…”
Section: Introductionmentioning
confidence: 99%
“…Patel et al, (2015) reported that Vigna mungo hydroalcoholic extract (VMHA) improved arthritic condition significantly by reducing pain and inflammation. Improvement in pain behavior could result from the inhibition of prostaglandins by flavonoids present in VMHA and/or maybe through central pathways of analgesia 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Vigna mungo has been reported pharmacologically to possess anti-inflammatory activity 32 . Anti-inflammatory activity is due to ethanol extracts mainly polyphenols 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Then the rats were induced to grasp rigid bars attached to a digital force gauge (Aikoh Engineering Corporation, Osaka, Japan) with their right hind limb. Each rat was gently pulled backward, and the tension reading of the digital force gauge was defined as the grip strength [ 21 ]. The test was performed three consecutive times, and the mean value of the three tests was recorded as the grip strength.…”
Section: Methodsmentioning
confidence: 99%